2023
DOI: 10.1002/adbi.202300130
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal DEHP Exposure Induces Premature Testicular Aging by Promoting Leydig Cell Senescence through the MAPK Signaling Pathways

Abstract: Previous studies show that prenatal di‐(2‐ethylhexyl) phthalate (DEHP) exposure induces premature testicular aging. However, the evidence is weak, and the underlying mechanisms remain unclear. p38/extracellular signal‐regulated kinase (ERK)/c‐Jun NH(2)‐terminal kinase (JNK) MAPK pathways participate in aging. Leydig cell (LC) senescence results in testicular aging. Whether prenatal DEHP exposure induces premature testicular aging by promoting LC senescence warrants further study. Here, male mice undergo prenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
4
1
0
Order By: Relevance
“…The protein expression of LHCGR and HSD3B2 was down-regulated after DEHP exposure ( Figure 2L-2O ). Partial results were similar to our previous study ( 29 ). Therefore, DEHP induced immediate testicular injury in the neonatal stage by interfering with steroidogenic gene expression.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The protein expression of LHCGR and HSD3B2 was down-regulated after DEHP exposure ( Figure 2L-2O ). Partial results were similar to our previous study ( 29 ). Therefore, DEHP induced immediate testicular injury in the neonatal stage by interfering with steroidogenic gene expression.…”
Section: Resultssupporting
confidence: 92%
“…These results were verified by WB analysis ( Figure 3L-3N ). Partial results were similar to our previous study ( 29 ). These results indicated that prenatal DEHP exposure induced DSD and adult male disorders by interfering with steroidogenic gene expression.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations